Age-dependent acquisition of IgG antibodies to Shigella serotypes—a retrospective analysis of seroprevalence in Kenyan children with implications for infant vaccination - Kapulu, Melissa C.; Muthumbi, Esther; Otieno, Edward; Rossi, Omar; Ferruzzi, Pietro; Necchi, Francesca; Acquaviva, Alessandra; Martin, Laura B.; Orindi, Benedict; Mwai, Kennedy; Kibet, Hillary; Mwanzu, Alfred; et al. (Frontiers in Immunology, 2024)
Background: Shigellosis mainly affects children under 5 years of age living in low-and-middle income countries, who are the target population for vaccination. There is however limited data available to define the appropriate timing for vaccine administration in this age group. Information on antibody responses following natural infection, proxy for exposure, could help guide vaccination strategies. Methods: We undertook a retrospective analysis of antibodies to 5 of the most prevalent Shigella serotypes among children aged <5 years in Kenya. Serum samples from a cross-sectional sero-survey in three Kenyan sites (Nairobi; Siaya; and Kilifi) were analysed by standardized ELISA to measure IgG against S. sonnei and S. flexneri 1b, 2a, 3a, and 6. We identified factors associated with seropositivity to each Shigella serotype, including seropositivity to other Shigella serotypes. Results: A total of 474 samples, one for each participant, were analyzed: Nairobi (n=169), Siaya (n=185), and Kilifi (n=120). Median age of participants was 13.4 months (IQR 7.0-35.6) and the male:female ratio was 1:1. Geometric Mean Concentrations (GMC) for each serotype increased with age, mostly in the second year of life. Overall seroprevalence of IgG antibodies increased with age except for S. flexneri 6 which was high across all age sub-groups. In the second year of life, there was a statistically significant increase of antibody GMCs against all 5 serotypes (p=0.01-0.0001) and a significant increase of seroprevalence for S. flexneri 2a (p=0.006), S. flexneri 3a (p=0.006), and S. sonnei (p=0.05) compared to second part of first year of life. Among all possible pairwise comparisons of antibody seropositivity, there was a significant association between S. flexneri 1b and 2a (OR=6.75, 95% CI 3-14, p<0.001) and between S. flexneri 1b and 3a (OR=23.85, 95% CI 11-54, p<0.001). Conclusion: Children living in low-and-middle income settings such as Kenya are exposed to Shigella infection starting from the first year of life and acquire serotype-specific antibodies against multiple serotypes. The data from this study suggest that Shigella vaccination should be targeted to infants, ideally at 6 or at least 9 months of age, to ensure children are protected in the second year of life when exposure significantly increases.